Fajar Shodiq Dalam Pandangan Mufassir Modern-Kontemporer Telaah Waktu Shalat Subuh - Sudarmadi Putra (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The definition of dawn shodiq that has been understood so far is the scattering of light on the eastern horizon, starting to become bright towards morning when the sun is -20 degrees below the eastern horizon. Fajr shodiq is a sign of the beginning of the dawn prayer time. Fajr is one of the five daily obligatory prayers which is a spiritual obligation for Muslims. The discourse on dawn shadiq and the beginning of Fajr time has emerged in at least the last eight years. Especially when some Muslim communities driven by Qiblati began to observe the dawn of sadiq in a number of places in the provinces of East Java, Central Java and the Special Region of Yogyakarta. Qiblati publishes the results physically and electronically. Qiblati claims that the start of dawn time in Indonesia is too fast, namely between 12 and 24 minutes compared to when shadiq dawn begins to be observed. If this Qiblati opinion is correlated with the position of the Sun, it is found that the beginning of Fajr time according to Qiblati occurs when the height of the Sun is between minus 17° to minus 14°